EXPLORING MFENSI CLAY FOR MAKING SOUVENIRS IN GHANA - Frank Paul Mathews, Nti; Steiner, Rudolf; Clement Frederick, Ampah; Panin Kwame Baah, Owusu; William, Daitey (Penerbit Lafadz Jaya, 2026)
The purpose of the research was to use Mfensi clay in the production of souvenirs for artistic, cultural and economic potentials in Ghana. The problem was with several local pottery centers in Ashanti Region like Pankrono, Afari and Mfensi, none of their products has been seen as souvenirs or being sold on the tourist market. The study sought in producing souvenirs from Mfensi Clay from selected designs from their characteristics. This study used studio-based research method by employing triangulated data collection tools of observation, interviews and photographs to analyse the data. The results indicated that Mfensi clay can be used for the production of souvenirs in diverse ways and help preserve the craft for future generations. The study recommended teaching local potters how to creatively create souvenirs from Mfensi beyond their functional objectives, stakeholders like the Kumasi Cultural Center and Ministry of Tourism and Culture should offer workshop programs at the various pottery settlements or centres to develop apprenticeships.